2010
DOI: 10.1091/mbc.e09-07-0572
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the AAA ATPase Vps4 on ESCRT-III

Abstract: A complex network of interactions mediates the recruitment of Vps4 to ESCRT-III and its subsequent assembly, two key steps in the ESCRT-dependent vesicle formation at the endosome. A model is presented depicting the order of events that lead to active, ESCRT-III–associated Vps4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
124
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 57 publications
14
124
0
Order By: Relevance
“…Nevertheless, our data are consistent with published models in which LIP5 and CHMP5 are initially tightly associated in the cytoplasm (53). Formation of stable ESCRT-III-associated LIP5-VPS4 complexes might then require both a direct LIP5(VSL)-VPS4(SAB) interaction and a supporting interaction between the CHMP1B MIM1 element and the first LIP5 MIT domain (33,45). It is not yet clear why CHMP5 is also required to form this complex, but it was recently shown that CHMP5 can bind the ALIX paralog BROX at a site located just downstream of the LIP5-binding site (77).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Nevertheless, our data are consistent with published models in which LIP5 and CHMP5 are initially tightly associated in the cytoplasm (53). Formation of stable ESCRT-III-associated LIP5-VPS4 complexes might then require both a direct LIP5(VSL)-VPS4(SAB) interaction and a supporting interaction between the CHMP1B MIM1 element and the first LIP5 MIT domain (33,45). It is not yet clear why CHMP5 is also required to form this complex, but it was recently shown that CHMP5 can bind the ALIX paralog BROX at a site located just downstream of the LIP5-binding site (77).…”
Section: Discussionsupporting
confidence: 92%
“…Our mutational and NMR spectroscopic data are consistent with a model in which the terminal helix of CHMP1B makes a MIM1-like interaction with the helix 2/3 groove of the first LIP5 MIT module. CHMP1B/Did2p is an unusual ESCRT-III protein in that it binds well to the MIT domains from both VPS4 and LIP5 (33,34,39,40,50,58). This is apparently possible because the helix 2/3 grooves of the MIT domains from VPS4 and LIP5 are similar in character.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations